2020
DOI: 10.1186/s40621-020-00262-1
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in triage and management of the homeless and the elderly trauma patient

Abstract: Background: Trauma systems are designed to provide specialized treatment for the most severely injured. As populations change, it is imperative for trauma centers to remain dynamic to provide the best care to all members of the community. Methods: A retrospective review of all trauma patients treated at one Level II trauma center in Southern CA over 5 years. Three cohorts of patients were studied: geriatric (> 65 years), the homeless, and all other trauma patients. Triage, hospitalization, and outcomes were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Within the subsample, there was a high ratio of patients who were assigned an ED RN and were subsequently left in the care of other ED RN team members when their primary ED RN was reallocated to a trauma patient. This supported previous studies’ suggestions that ED staffing models may need to incorporate coverage for non-trauma patients during a trauma response alert [ 1 , 4 , 12 ]. When analyzing whether registered nurses were deployed to lower-level acuity patients in the subsample, the majority of patients were a level 2, which would indicate a need for a revision to the trauma team or the ED staffing model for an appropriate trauma response [ 3 , 5 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Within the subsample, there was a high ratio of patients who were assigned an ED RN and were subsequently left in the care of other ED RN team members when their primary ED RN was reallocated to a trauma patient. This supported previous studies’ suggestions that ED staffing models may need to incorporate coverage for non-trauma patients during a trauma response alert [ 1 , 4 , 12 ]. When analyzing whether registered nurses were deployed to lower-level acuity patients in the subsample, the majority of patients were a level 2, which would indicate a need for a revision to the trauma team or the ED staffing model for an appropriate trauma response [ 3 , 5 ].…”
Section: Discussionsupporting
confidence: 87%
“…Underdeployment of the trauma team in the emergency department (ED) can result in delays in patient triage and treatment, increased risk for complications, and increased mortality [3,8,9]; while overdeployment can also increase patient risk, staff burnout, and excess burden on trauma center resources [2,4,10]. Additionally, disparities in the deployment of resources have been noted within certain patient populations triaged to lower levels of trauma response (e.g., geriatric, blunt non-penetrating trauma victims) [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The present study builds on existing literature of increased hospital resource use among people experiencing homelessness . Reasons for increased LOS among people experiencing homelessness are multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…The present study builds on existing literature of increased hospital resource use among people experiencing homelessness. 32 , 33 , 34 Reasons for increased LOS among people experiencing homelessness are multifactorial. It may be driven in part by low socioeconomic status; patients with social and/or material deprivation have been shown to have longer LOS compared with patients with higher socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…40 Certain populations including older adults, females, and patients belonging to racial and ethnic minority groups present an additional challenge to trauma triage. [41][42][43][44] Compared with appropriately triaged adult patients, undertriaged older adult patients have a twofold increased risk of mortality and a 50% increased risk of complications. 12 Prior studies have reported an undertriage rate of up to 61% for severely injured older adults, 42 and the TIP-NEI-6 undertriage rate was much closer to the suggested ACSCOT rate at 8.4%.…”
Section: Discussionmentioning
confidence: 99%